Cerebral Malaria Is Regulated by Host-Mediated Changes in Plasmodium Gene Expression - Clare K. Cimperman; Mirna Pena; Sohret M. Gokcek; Brandon P. Theall; Meha V. Patel; Anisha Sharma; ChenFeng Qi; Daniel Sturdevant; Louis H. Miller; Patrick L. Collins; Susan K. Pierce; Munir Akkaya (mBio, 2023)
ABSTRACT Cerebral malaria (CM), the deadliest complication of Plasmodium infection, is a complex and unpredictable disease. However, our understanding of the host and parasite factors that cause CM is limited. Using a mouse model of CM, experimental CM (ECM), we performed a three-way comparison between ECM-susceptible C57BL/6 mice infected with ECM-causing Plasmodium ANKA parasites [ANKA(C57BL/6)], ECM-resistant BALB/c mice infected with Plasmodium ANKA [ANKA(BALB/c)], and C57BL/6 mice infected with Plasmodium NK65 that does not cause ECM [NK65(C57BL/6)]. All ANKA(C57BL/6) mice developed CM. In contrast, in ANKA(BALB/c) and NK65(C57BL/6), infections do not result in CM and proceed similarly in terms of parasite growth, disease course, and host immune response. However, parasite gene expression in ANKA(BALB/c) was remarkably different than that in ANKA(C57BL/6) but similar to the gene expression in NK65(C57BL/6). Thus, Plasmodium ANKA has an ECM-specific gene expression profile that is activated only in susceptible hosts, providing evidence that the host has a critical influence on the outcome of infection. IMPORTANCE Hundreds of thousands of lives are lost each year due to the brain damage caused by malaria disease. The overwhelming majority of these deaths occur in young children living in sub-Saharan Africa. Thus far, there are no vaccines against this deadly disease, and we still do not know why fatal brain damage occurs in some children while others have milder, self-limiting disease progression. Our research provides an important clue to this problem. Here, we showed that the genetic background of the host has an important role in determining the course and the outcome of the disease. Our research also identified parasite molecules that can potentially be targeted in vaccination and therapy approaches.